Cysticerci Drive Dendritic Cells to Promote In Vitro and In Vivo Tregs Differentiation - Laura Adalid-Peralta; Asiel Arce-Sillas; Gladis Fragoso; Graciela Cárdenas; Marcos Rosetti; Didier Casanova-Hernández; Claudia Rangel-Escareño; Laura Uribe-Figueroa; Agnes Fleury; Edda Sciutto (Clinical and Developmental Immunology)
Regulatory T cells (Tregs) play a crucial role in immune homeostasis. Treg induction is a strategy that parasites have evolved to modulate the host’s inflammatory environment, facilitating their establishment and permanence. In human Taenia solium neurocysticercosis (NC), the concurrence of increased peripheral and central Treg levels and their capacity to inhibit T cell activation and proliferation support their role in controlling neuroinflammation. This study is aimed at identifing possible mechanisms of Treg induction in human NC. Monocyte-derived dendritic cells (DC) from healthy human donors, cocultivated with autologous CD4+ naïve cells either in the presence or absence of cysticerci, promoted CD25highFoxp3+ Treg differentiation. An increased Treg induction was observed when cysticerci were present. Moreover, an augmentation of suppressive-related molecules (SLAMF1, B7-H1, and CD205) was found in parasite-induced DC differentiation. Increased Tregs and a higher in vivo DC expression of the regulatory molecules SLAMF1 and CD205 in NC patients were also found. SLAMF1 gene was downregulated in NC patients with extraparenchymal cysticerci, exhibiting higher inflammation levels than patients with parenchymal parasites. Our findings suggest that cysticerci may modulate DC to favor a suppressive environment, which may help parasite establishment, minimizing the excessive inflammation, which may lead to tissue damage.